2021
DOI: 10.1016/j.semcdb.2021.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Forced into shape: Mechanical forces in Drosophila development and homeostasis

Abstract: Mechanical forces play a central role in shaping tissues during development and maintaining epithelial integrity in homeostasis. In this review, we discuss the roles of mechanical forces in Drosophila development and homeostasis, starting from the interplay of mechanics with cell growth and division. We then discuss several examples of morphogenetic processes where complex 3D structures are shaped by mechanical forces, followed by a closer look at patterning processes. We also review the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 161 publications
(188 reference statements)
0
5
0
Order By: Relevance
“…We generate these lesions in a consistent region of the wing (Fig. 1B) because mechanical stresses inevitably will vary across the developing wing and can influence wound re-epithelialisation (Etournay et al, 2015; Paci & Mao, 2021; Popović et al, 2017; Turley et al, 2023). The wing at this developmental stage consists of two flattened epithelial sheets with intervening hemolymph, in which resides innate immune cells (called hemocytes in Drosophila ) and fat body cells ((Franz et al, 2018) and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We generate these lesions in a consistent region of the wing (Fig. 1B) because mechanical stresses inevitably will vary across the developing wing and can influence wound re-epithelialisation (Etournay et al, 2015; Paci & Mao, 2021; Popović et al, 2017; Turley et al, 2023). The wing at this developmental stage consists of two flattened epithelial sheets with intervening hemolymph, in which resides innate immune cells (called hemocytes in Drosophila ) and fat body cells ((Franz et al, 2018) and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We chose to develop, and test the capability of, our model using the epithelium of the Drosophila pupal wing because of the optical translucency and genetic tractability of Drosophila , which makes it easy to generate tissues with fluorescently labelled nuclei and cell boundaries (Etournay et al, 2015; George & Martin, 2022; Mao et al, 2011). The Drosophila pupal wing epithelium undergoes extensive growth through rapid cell divisions early in pupal life (Athilingam et al, 2021; Paci & Mao, 2021), and can be imaged with high spatio-temporal resolution using live confocal microscopy. Drosophila pupae at 18 hours after puparium formation (APF) are removed from their brittle, opaque puparium to reveal the transparent pupal wing (Weavers et al, 2018) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Supporting this hypothesis, studies have reported that crowding could induce live cell extrusion, as a way to preserve a constant cell number. 52 , 53 Moreover, dividing cells have been shown to generate protrusive forces upon mitosis 54 : however, if the forces are insufficient to deform the surrounding environment, mitosis will fail, and cells can either disassemble the mitotic spindle and reintegrate the chromosomes, or undergo apoptosis. 54 Furthermore, at the molecular level, E-cadherin has been shown to be capable of forcing homeostatic conditions by reprogramming cell migration and cell cycle.…”
Section: Discussionmentioning
confidence: 99%